2014
DOI: 10.1128/aac.02274-13
|View full text |Cite
|
Sign up to set email alerts
|

Ceftaroline Restores Daptomycin Activity against Daptomycin-Nonsusceptible Vancomycin-Resistant Enterococcus faecium

Abstract: c Daptomycin-nonsusceptible vancomycin-resistant Enterococcus faecium (VRE) strains are a formidable emerging threat to patients with comorbidities, leaving few therapeutic options in cases of severe invasive infections. Using a previously characterized isogenic pair of VRE strains from the same patient differing in their daptomycin susceptibilities (Etest MICs of 0.38 mg/liter and 10 mg/liter), we examined the effect of ceftaroline, ceftriaxone, and ampicillin on membrane fluidity and susceptibility of VRE to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
68
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 23 publications
3
68
0
Order By: Relevance
“…LL37 is not only a marker of immune response but also an endogenous analogue to DAP (49). Our data echo previous findings demonstrating the synergistic effects of ␤-lactam agents on LL37 activity in E. faecalis, E. faecium, and Staphylococcus aureus (24,25,50,51). From the available data, it appears that ␤-lactams have the ability to amplify both portions of the innate immune response (LL37) and DAP activity against enterococci and that this augmentation of DAP activity may explain the enhancement we have demonstrated.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…LL37 is not only a marker of immune response but also an endogenous analogue to DAP (49). Our data echo previous findings demonstrating the synergistic effects of ␤-lactam agents on LL37 activity in E. faecalis, E. faecium, and Staphylococcus aureus (24,25,50,51). From the available data, it appears that ␤-lactams have the ability to amplify both portions of the innate immune response (LL37) and DAP activity against enterococci and that this augmentation of DAP activity may explain the enhancement we have demonstrated.…”
Section: Discussionsupporting
confidence: 81%
“…Mechanistically, it appears that these ␤-lactams decrease the surface charge of enterococcal cells and increase DAP binding to confer their synergistic effects (23)(24)(25). Two of these studies also demonstrated that AMP and CPT restore not only DAP activity but also endogenous, cationic antimicrobial peptide activity, demonstrating that the effect ␤-lactams have on membrane charge may be imperative for the synergistic effect (24,25).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Synergy between daptomycin and beta-lactams is believed to be mediated through beta-lactam-induced alterations in surface charge that facilitate an increase in daptomycin binding, leading to enhanced membrane depolarization (23)(24)(25)(26)(27)(28). Since fosfomycin also disrupts cell wall synthesis, it could be theorized that there is a similar mechanism that drives the synergy that has been observed with daptomycin and fosfomycin.…”
mentioning
confidence: 99%